2019
DOI: 10.3389/fnbeh.2019.00199
|View full text |Cite
|
Sign up to set email alerts
|

Neural Sensitivity to Social and Monetary Reward in Depression: Clarifying General and Domain-Specific Deficits

Abstract: Reward dysfunction is thought to be play a critical role in the pathogenesis of depression. Multiple studies have linked depression to abnormal neural sensitivity to monetary rewards, but it remains unclear whether this reward dysfunction is generalizable to other rewards types. The current study begins to address this gap by assessing abnormal sensitivity to both monetary and social rewards in relation to depressive symptoms. We recorded event-related potentials (ERPs) during two incentive delay tasks, one wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 87 publications
14
57
1
Order By: Relevance
“…Consistent with the aspect of reward responsiveness probed by these tasks, ERP indices of reward processing included the P2 (attention selection and salience detection), P3 (attention reallocation when task demands change or an update of task representations is needed), and FN/ FRN/ RewP, but, except for (Oumeziane et al., 2019), none assessed the Cue P3 or SPN and none assessed the Target P3. Regarding self‐report measures, across available studies, measures were either based on outdated conceptualizations of the RST‐P (De Pascalis et al., 2010; Lange et al., 2012; Van den Berg et al., 2011) or assessed reward responsiveness narrowly but not reinforcement sensitivity broadly (Bress & Hajcak, 2013; Kujawa et al., 2019; Oumeziane et al., 2019; Salim et al., 2015). Accordingly, assessment of convergent validity between ERP components reflecting initial responsiveness to reward attainment and reward anticipation and self‐report indices of reinforcement sensitivity (in keeping with most recent theoretical conceptualizations) in adolescents —fills an important gap in the literature.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Consistent with the aspect of reward responsiveness probed by these tasks, ERP indices of reward processing included the P2 (attention selection and salience detection), P3 (attention reallocation when task demands change or an update of task representations is needed), and FN/ FRN/ RewP, but, except for (Oumeziane et al., 2019), none assessed the Cue P3 or SPN and none assessed the Target P3. Regarding self‐report measures, across available studies, measures were either based on outdated conceptualizations of the RST‐P (De Pascalis et al., 2010; Lange et al., 2012; Van den Berg et al., 2011) or assessed reward responsiveness narrowly but not reinforcement sensitivity broadly (Bress & Hajcak, 2013; Kujawa et al., 2019; Oumeziane et al., 2019; Salim et al., 2015). Accordingly, assessment of convergent validity between ERP components reflecting initial responsiveness to reward attainment and reward anticipation and self‐report indices of reinforcement sensitivity (in keeping with most recent theoretical conceptualizations) in adolescents —fills an important gap in the literature.…”
Section: Introductionmentioning
confidence: 85%
“…In the remaining investigations, reward learning (and response to reward during learning) was probed in a double choice Go/No-Go task (De Pascalis et al, 2010), and reward expectation mismatch was probed in a choice task (Lange et al, 2012). Consistent with the aspect of reward responsiveness probed by these tasks, ERP indices of reward processing included the P2 (attention selection and salience detection), P3 (attention reallocation when task demands change or an update of task representations is needed), and FN/ FRN/ RewP, but, except for (Oumeziane et al, 2019), none assessed the Cue P3 or SPN and none assessed the Target P3. Regarding self-report measures, across available studies, measures were either based on outdated conceptualizations of the RST-P (De Pascalis et al, 2010;Lange et al, 2012;Van den Berg et al, 2011) or assessed reward responsiveness narrowly but not reinforcement sensitivity broadly (Bress & Hajcak, 2013;Kujawa et al, 2019;Oumeziane et al, 2019;Salim et al, 2015).…”
Section: Convergent Predictive and Incremental Validity Of Neuralmentioning
confidence: 97%
See 2 more Smart Citations
“…Using healthy samples, recent ERP studies have demonstrated that monetary and social rewards elicit morphologically similar ERPs during both the anticipatory and consummatory phases of reward processing. Specifically, whereas the SPN and the fb-P3 were found to be enhanced for monetary rewards than social rewards, the RewP seemed to be comparable across reward types ( Ait Oumeziane et al , 2017 ; Distefano et al , 2018 ; Ait Oumeziane et al , 2019 ; but see Ethridge and Weinberg, 2018 ). To our knowledge, only one previous study using a reversal learning task found that the RewP in response to monetary rewards was unaffected by social anhedonia as determined by the Revised Chapman Social Anhedonia Scale (RSAS; Karcher et al , 2017 ).…”
Section: Introductionmentioning
confidence: 90%